Moisture as an indicator of the manifestation of hazardous properties of coal seams - Є.С. Руднєв; А.М. Гальченко; В.Ю. Тарасов; М.І. Антощенко (Геофизический журнал, 2022)
Purpose: establish the change in the ratios between individual types of moisture and indicators of metamorphic transformations of coal seams after recalculating their values for the working state of the fuel. This will make it possible to predict the manifestation of hazardous properties mining.